SOSIOLOGI OLAHRAGA DAN PEMBENTUKAN SOLIDARITAS SOSIAL: STUDI LITERATUR - Rezky Agung Daulay; Jemli Faomusoso Daeli; Yulfi Sani Efendi; Ferdinand Bondar; M. Roihan Heriandi; Fauzan Rahmi; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sport not only functions as a physical activity but also plays a vital role in social life. From a sociological perspective, sport serves as a means of social interaction that fosters cooperation, a sense of togetherness, and social solidarity between individuals and groups. This study aims to analyze the role of sport in fostering social solidarity through a literature review approach. The method used is a literature review, compiling various sources, including books and scientific journals, relevant to the sociology of sport and social solidarity. The results indicate that sporting activities can strengthen social relationships, enhance sportsmanship, foster a sense of unity, and foster positive social interactions within the community. Furthermore, both traditional and modern sports play a role in maintaining cultural values and strengthening relationships between social groups. Thus, sport plays a significant role in building social solidarity and creating a more harmonious community life.